Endothelial Barrier Integrity Is Disrupted In Vitro by Heme and by Serum From Sickle Cell Disease Patients - Santaterra, Vanessa Araujo Gomes; Fiusa, Maiara Marx Luz; Hounkpe, Bidossessi Wilfried; Chenou, Francine; Tonasse, Wouitchekpo Vincent; da Costa, Loredana Nilkenes Gomes; Garcia-Weber, Diego; Domingos, Igor de Farias; Lima, Franciele de; Borba-Junior, Ivanio Teixeira; Araújo, Aderson da Silva; Lucena-Araújo, Antonio Roberto; et al. (Frontiers in Immunology, 2020)
Free extracellular heme has been shown to activate several compartments of innate immunity, acting as a danger-associated molecular pattern (DAMP) in hemolytic diseases. Although localized endothelial barrier (EB) disruption is an important part of inflammation that allows circulating leukocytes to reach inflamed tissues, non-localized/deregulated disruption of the EB can lead to widespread microvascular hyperpermeability and secondary tissue damage. In mouse models of sickle cell disease (SCD), EB disruption has been associated with the development of a form of acute lung injury that closely resembles acute chest syndrome (ACS), and that can be elicited by acute heme infusion. Here we explored the effect of heme on EB integrity using human endothelial cell monolayers, in experimental conditions that include elements that more closely resemble in vivo conditions. EB integrity was assessed by electric cell-substrate impedance sensing in the presence of varying concentrations of heme and sera from SCD patients or healthy volunteers. Heme caused a dose-dependent decrease of the electrical resistance of cell monolayers, consistent with EB disruption, which was confirmed by staining of junction protein VE-cadherin. In addition, sera from SCD patients, but not from healthy volunteers, were also capable to induce EB disruption. Interestingly, these effects were not associated with total heme levels in serum. However, when heme was added to sera from SCD patients, but not from healthy volunteers, EB disruption could be elicited, and this effect was associated with hemopexin serum levels. Together our in vitro studies provide additional support to the concept of heme as a DAMP in hemolytic conditions.